(3cjajI cTa GdCMcGe hGdUaGJ Yf NUGFU GdeDKQGJ hGdebJVjGJs - (3CHh eMeO GdMSf Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B584 (3g` s ((3YR GdOjf Hf GdMSf Hf CejQ GdeDefjf s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg CeG HYO aEf HYV GdENhGf deG QCi cdGe ef JbOe ef GdeJcdejf ai GdUaGJ hGdCMcGe dGjcGO jTai Zdjd GdUOhQ SCdfi Cf ChQO ai Pdc LedkG fGaYI aCLHJg Edi eG SCd s
(3BNQgG (B:s
(3hCf jhabfi dENdGU GdbUO hGdfjI ai eG CJYGWGg ai eSJbHd CjGei Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3hebGHdI s
(3cJHJ GdahGJM HGdSejc s
(3Ydi ZGTjJgG ebGHdI hbQGAI eDQNI SfI (B1046(3g` HBNQgG CHjGJ ddefUhQ HGddg YHO Gddg Hf MeRI cJHgG dTjNg GdQUGU s
Keywords: (3GdJhMjO hGdedd hGdfMds